Russell, Peter (London, 2013)
2013 "Russell, Peter", 2013, HistoryTalk Peter Russell was fascinated with animals as a child and wanted to go into veterinary work. He left school at 15 without qualifications and became a technician at various hospitals, including Great Ormond Street, Hammersmith, and the Institute of Child Health. He describes how he was encouraged to study and develop his career (he was mentored by a work colleague). He studied part time at a technical college and gradually worked towards a Fellowship. He mentions that his employers were quite advanced for the time in terms of equal opportunities. He went on to work at University College. He describes pay scales, promotion and the relative job security. He worked on various developments in medicine including cancer research (working for Cancer Research Campaign), the CJD and SARS outbreaks and various positive breakthroughs in science.